Method for constructing egg white derived iron single atom doped porous carbon material by soft and hard templates, and products and applications thereof
Patent Information
- Application Number
- CN202610960552.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]针对现有聚合物基复合材料中电磁波吸收性能与热传导性能难以协同提升,以及现有金属单原子掺杂多孔碳材料制备过程复杂、成本较高、孔结构与金属单原子位点难以同步调控等问题,本发明提供了一种软硬双模板构筑蛋清衍生铁单原子掺杂多孔碳材料的方法,本发明采用蛋清作为生物质前驱体,通过强力搅拌形成稳定蛋白泡沫,利用蛋白泡沫中的气泡作为软模板和造孔单元,并以氯化钠作为硬模板和造孔剂,经冷冻干燥、惰性气氛热解和模板去除处理,制备得到具有三维蜂窝状多尺度孔结构的铁单原子掺杂多孔碳材料
1.原料绿色、工艺简单、成本低廉:本发明以来源广泛、可再生的蛋清为生物质前驱体,其可同时提供碳源、氮源及铁元素来源,以廉价易得的氯化钠作为硬模板和造孔剂,并利用搅拌形成的蛋白泡沫中的气泡作为软模板和造孔单元,无需额外引入昂贵金属盐、复杂有机配体、化学活化剂或强腐蚀性蚀刻剂。整个制备过程主要包括混合、搅拌发泡、冷冻干燥、热解和水洗步骤,工艺流程简单,操作条件温和,成本较低,具有较好的环境友好性和规模化制备潜力。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a method for constructing egg white-derived iron-doped porous carbon materials using a soft and hard dual-template approach. Specifically, it relates to a method for constructing iron-doped porous carbon materials using egg white as a biomass precursor and using air bubbles in protein foam and sodium chloride as soft and hard templates, respectively. It also relates to the iron-doped porous carbon materials prepared according to this method, as well as composite materials obtained by combining the iron-doped porous carbon materials with polytetrafluoroethylene. Furthermore, it relates to the applications of these materials in the fields of electromagnetic wave absorption, electromagnetic interference suppression, and thermal management, belonging to the technical fields of electromagnetic functional materials and thermal management composite materials. Background Technology
[0002] With the rapid development of electronic devices towards lighter weight, higher integration, and higher power density, the electromagnetic environment inside electronic devices is becoming increasingly complex, and the problem of localized heat accumulation is becoming more prominent. While compact circuit layouts are beneficial for improving device performance and integration levels, they also exacerbate electromagnetic interference and compress heat dissipation space, thereby affecting signal transmission stability, device reliability, and lifespan. Therefore, developing multifunctional composite materials that can simultaneously achieve electromagnetic wave absorption, electromagnetic interference suppression, and heat conduction within a limited space has become a crucial technical problem that urgently needs to be solved in fields such as high-performance electronic packaging, communication equipment, and intelligent electronic devices.
[0003] Polytetrafluoroethylene (PTFE) possesses excellent chemical stability, temperature resistance, flexibility, and processing properties, making it a promising candidate for applications in electronic packaging and thermal interface materials. However, PTFE itself has low thermal conductivity and limited attenuation capabilities for electromagnetic waves, making it difficult to meet the comprehensive requirements of modern electronic devices for heat dissipation and electromagnetic compatibility. Functional fillers are typically introduced into the polymer matrix to improve its thermal conductivity and electromagnetic wave absorption performance. However, existing filler systems still have certain limitations: fillers for electromagnetic wave absorption usually rely on mechanisms such as dielectric loss, magnetic loss, or interfacial polarization, but their structural design may lead to discontinuous heat conduction pathways; fillers used to improve thermal conductivity often require the formation of a continuous heat transfer network, which may cause impedance mismatch or insufficient electromagnetic energy dissipation capacity. Therefore, achieving a balance between electromagnetic wave absorption, impedance matching, and thermal conductivity within the same polymer composite system remains a significant challenge.
[0004] Carbon materials, with their low density, tunable structure, tunable dielectric properties, and certain thermal conductivity, are important candidate fillers for constructing composite materials for electromagnetic wave absorption and thermal management. In particular, porous carbon materials can improve electromagnetic wave transmission paths and impedance matching through pore structure modulation, and enhance polarization loss through abundant interfacial structures. However, traditional carbon materials often suffer from problems such as dense structure, uniform pore size, insufficient interfacial polarization centers, or excessive continuity of conductive networks, which can easily lead to enhanced electromagnetic wave reflection or limited absorption bandwidth. Furthermore, simply relying on the carbon framework to improve thermal conductivity is insufficient to simultaneously achieve good electromagnetic wave attenuation and stable impedance matching. In recent years, atomically dispersed metal site doping of carbon materials has been considered an effective way to modulate the electronic structure, polarization behavior, and energy transfer characteristics of carbon materials. Metal single-atom sites can induce local charge redistribution through coordination with surrounding carbon / nitrogen atoms, increasing polarization centers and modulating the local structure of the carbon framework, thereby potentially improving electromagnetic wave absorption and thermal conductivity. However, existing methods for preparing metal-doped porous carbon materials typically require the addition of metal salts, complex ligands, special templates, or post-processing etching, which can lead to cumbersome processes, high costs, insufficient stability of metal sites, and difficulties in synergistically controlling pore structure and single-atom sites. Furthermore, the controllable preparation of multi-scale porous carbon structures usually relies on methods such as hard templates, soft templates, or chemical activation. Single-template methods often struggle to simultaneously construct macroscopic interconnected channels and micro / mesoporous structures, limiting the synergistic optimization of electromagnetic wave multiple reflections, interface polarization, and heat conduction paths. The dual-template strategy (hard and soft) provides a feasible approach for constructing multi-scale porous carbon materials, where soft templates can be used to form larger channels or honeycomb structures, while hard templates can be used to support the carbon framework and further control the pore structure. However, how to utilize green, low-cost biomass precursors to simultaneously achieve pore formation using soft and hard templates, stable metal single-atom doping, and the construction of three-dimensional porous carbon networks through a simple process remains a key technical challenge to be solved in this field.
[0005] Therefore, there is an urgent need to develop a method for preparing metal single-atom doped porous carbon electromagnetic wave absorbing materials that uses green raw materials, has a simple process, a controllable structure, and is suitable for composite applications. This method aims to achieve the synergistic construction of multi-scale porous structures, atomically dispersed metal sites, and a continuous carbon skeleton, and further apply these materials to polymer-based composite materials such as polytetrafluoroethylene, thereby obtaining composite materials that combine electromagnetic wave absorption, electromagnetic interference suppression, and thermal management functions. Summary of the Invention
[0006] To address the challenges of synergistically improving electromagnetic wave absorption and thermal conductivity in existing polymer-based composite materials, and the complex, costly, and difficult-to-synchronize pore structure and metal single-atom site control processes in the preparation of existing metal single-atom doped porous carbon materials, this invention provides a method for constructing egg white-derived iron single-atom doped porous carbon materials using a soft-hard dual-template approach. This invention utilizes egg white as a biomass precursor, forming stable protein foam through vigorous stirring. The bubbles within the protein foam serve as soft templates and pore-forming units, while sodium chloride acts as a hard template and pore-forming agent. Through freeze-drying, inert atmosphere pyrolysis, and template removal, iron single-atom doped porous carbon materials with a three-dimensional honeycomb multi-scale pore structure are prepared. This method is simple to operate, uses readily available and inexpensive green raw materials, offers controllable pore structure, and exhibits good iron single-atom dispersion, making it suitable for industrial applications.
[0007] The specific technical solution of the present invention is as follows: A method for constructing egg white-derived iron-doped porous carbon materials using a soft and hard dual-template approach includes the following steps: (1) Mix egg whites with sodium chloride and stir vigorously to form stable protein foam; (2) The protein foam obtained in step (1) is freeze-dried under vacuum to obtain a porous protein precursor; (3) The porous protein precursor obtained in step (2) is subjected to pyrolysis under an inert atmosphere; (4) After pyrolysis, the product is cooled, the sodium chloride template is removed by washing with water, and then dried to obtain iron single-atom doped porous carbon material (EC).
[0008] Furthermore, in step (1), the egg white is natural, unmodified, commercially available egg white, requiring no further purification. As a natural source of carbon, nitrogen, sulfur, and iron, the egg white requires no additional metal salts, organic ligands, or dopants. The raw material is widely available, environmentally friendly, and inexpensive.
[0009] Furthermore, in step (1), egg white and sodium chloride are mixed and vigorously stirred to form a stable protein foam; wherein, the bubbles in the protein foam serve as soft templates and pore-forming units, and the sodium chloride serves as hard templates and pore-forming agents. The bubbles and sodium chloride work synergistically to guide the formation of a porous carbon framework during freeze-drying and subsequent pyrolysis. After pyrolysis, sodium chloride is removed by washing with water, thereby obtaining a honeycomb-like three-dimensional multi-scale hierarchical porous carbon structure.
[0010] Furthermore, in step (1), the mass ratio of egg white to sodium chloride is 1:1-4.
[0011] Furthermore, in step (1), the stirring speed is greater than or equal to 800 r / min, for example 800 r / min, 900 r / min, 1000 r / min, 1100 r / min, 1500 r / min.
[0012] Furthermore, in step (2), the protein foam obtained in step (1) is placed under vacuum conditions for freeze drying to completely remove moisture and obtain a loose and porous white solid porous protein precursor. Furthermore, in step (3), the pyrolysis temperature is 750-850℃ and the pyrolysis time is 2-3h. During the pyrolysis process, the ferritin derived from egg white decomposes in situ, the carbon source is transformed into a three-dimensional carbon skeleton, and at the same time, the iron element is stably anchored in the carbon matrix in an atomic form.
[0013] Furthermore, in step (3), the inert atmosphere is provided by inert gases such as nitrogen and argon, preferably high-purity argon. The pyrolysis treatment is carried out under a continuously flowing inert gas, which can effectively isolate oxygen, prevent the material from being oxidized at high temperatures, and ensure the integrity of the carbon skeleton and the stable formation of iron single-atom sites.
[0014] Furthermore, in step (4), after pyrolysis, the material is naturally cooled to room temperature, and the resulting black product is repeatedly washed with deionized water to completely remove the sodium chloride template used as a pore-forming agent; subsequently, it is dried at 50-80℃ to obtain the final iron-doped porous carbon material. The porous carbon is honeycomb-shaped and has a hierarchical pore structure composed of micropores, mesopores, and macropores, with a specific surface area of 180.29-209.68 m². 2 g -1 This three-dimensional interconnected, multi-scale porous system not only provides rich interfaces for electromagnetic waves to induce interface polarization and multiple scattering, but also facilitates the efficient transmission of phonons.
[0015] Furthermore, in step (4), iron exists uniformly in the carbon matrix in an atomically dispersed form, and forms Fe-N with nitrogen atoms in the carbon framework. x The Fe-N complex achieves stability through its coordination structure. x The structure is not only a powerful dipole polarization center that can significantly enhance dielectric loss, but it also facilitates electron transport and promotes local ordering of the carbon skeleton, which plays a positive role in maintaining high thermal conductivity.
[0016] This invention utilizes egg white as a biomass precursor and bubbles in protein foam and sodium chloride as soft and hard templates, respectively, to prepare iron-doped three-dimensional porous carbon materials through freeze-drying, pyrolysis, and template removal. Egg white provides carbon and nitrogen sources and facilitates the dispersion and anchoring of iron species; bubbles and sodium chloride synergistically create pores, forming a connected porous carbon framework; atomically dispersed iron single-atom sites can induce local charge redistribution, enhancing polarization loss and electromagnetic wave attenuation. This iron-doped porous carbon material possesses a multi-scale porous structure, a continuous carbon framework, and atomically dispersed iron single-atom sites, effectively improving impedance matching, enhancing dielectric loss, and thus improving electromagnetic wave attenuation. This iron-doped porous carbon material is also within the scope of this invention.
[0017] This invention also provides an iron single-atom-doped porous carbon / polytetrafluoroethylene composite material, which is obtained by combining the aforementioned iron single-atom-doped porous carbon material (EC) with polytetrafluoroethylene (PTFE). This composite material utilizes the synergistic effect between the three-dimensional interconnected carbon framework, multi-scale porous structure, and iron single-atom sites to achieve synergistic advantages in improving impedance matching, enhancing electromagnetic wave loss, and constructing heat conduction paths. It combines electromagnetic wave absorption and thermal management performance, achieving simultaneous improvement in both electromagnetic wave absorption and thermal management performance.
[0018] Furthermore, the iron-doped porous carbon material accounts for 15 wt% of the total mass of the iron-doped porous carbon material and polytetrafluoroethylene, meaning the filling amount of the iron-doped porous carbon material is 15 wt%. At this ratio, the iron-doped porous carbon material (EC) can form a continuous and effective three-dimensional network structure in the PTFE matrix. This not only constructs efficient electromagnetic loss and heat conduction pathways but also avoids the deterioration of matrix processing performance or interface problems caused by excessive filler, achieving the best balance between electromagnetic absorption performance and thermal conductivity.
[0019] Furthermore, the composite material can be a sheet or a component of various shapes. The preparation method is as follows: Iron-doped porous carbon material is mixed evenly with polytetrafluoroethylene emulsion, ethanol is added for demulsification, and the mixture is continuously stirred until it becomes dough-like; subsequently, the resulting dough-like mixture is placed in a mold and pressed at room temperature under a molding pressure of 5-10 MPa.
[0020] Furthermore, the composite material exhibits excellent electromagnetic wave absorption performance in the 2-18 GHz frequency range (with a test sample thickness of 2.00 mm), and its minimum reflection loss (RL) is [missing information]. min It can reach -55.47 dB, and the effective absorption bandwidth (EAB, RL < -10 dB) can reach 7.92 GHz.
[0021] Furthermore, the thermal conductivity of the composite material is significantly higher than that of pure polytetrafluoroethylene, reaching 0.45 W·m. -1 ·K -1 It exhibits rapid thermal response and excellent thermal cycle stability in actual heating-cooling cycles, demonstrating good active thermal management capabilities.
[0022] The present invention also provides the application of the above-mentioned iron single-atom doped porous carbon material and the above-mentioned iron single-atom doped porous carbon / polytetrafluoroethylene composite material in electromagnetic wave absorbing materials, electromagnetic interference suppression materials, thermal interface materials, and thermal management composite materials.
[0023] The present invention also provides the application of the above-mentioned iron single-atom doped porous carbon material and the above-mentioned iron single-atom doped porous carbon / polytetrafluoroethylene composite material in fields such as electronic packaging, radar stealth coating, and communication equipment that require integrated electromagnetic protection and thermal management solutions.
[0024] Compared with the prior art, the present invention has the following significant advantages: 1. Green raw materials, simple process, and low cost: This invention uses widely available and renewable egg white as a biomass precursor, which can simultaneously provide carbon, nitrogen, and iron sources. Inexpensive and readily available sodium chloride is used as a hard template and pore-forming agent, and air bubbles in the protein foam formed by stirring are used as soft templates and pore-forming units. There is no need to introduce expensive metal salts, complex organic ligands, chemical activators, or highly corrosive etchants. The entire preparation process mainly includes mixing, stirring and foaming, freeze-drying, pyrolysis, and washing steps. The process is simple, the operating conditions are mild, and the cost is low, exhibiting good environmental friendliness and potential for large-scale preparation.
[0025] 2. Synergistic Pore Formation with Soft and Hard Templates for Controllable Material Structure: This invention utilizes the synergistic effect of soft templates (bubbles) and hard templates (sodium chloride) in protein foam to construct a three-dimensional honeycomb-like multi-scale porous carbon network during pyrolysis and template removal. Bubbles, acting as soft templates, facilitate the formation of larger interconnected channels and honeycomb structures, while sodium chloride, acting as a hard template and pore-forming agent, supports the carbon framework and further regulates the pore structure. This synergistic effect enables the joint construction of macroscopic channels, mesopores, and micropores, thereby improving electromagnetic wave transmission paths, the number of interfaces, and structural stability.
[0026] 3. Stable dispersion of iron single-atom sites, enhanced electromagnetic loss capability: This invention utilizes the coordination and confinement of iron species by protein molecules in egg white to achieve atomic-level dispersion of iron during pyrolysis, forming stable iron single-atom sites or Fe–N sites. x Coordination structure. This structure can induce local charge redistribution, increase polarization centers, enhance interfacial polarization, dipole polarization and conductivity loss, and improve impedance matching together with the porous carbon framework, thereby improving the material's ability to attenuate electromagnetic waves.
[0027] 4. Synergistic Improvement of Electromagnetic Wave Absorption and Thermal Management Performance: The egg white-derived iron-doped porous carbon material obtained in this invention can be used as a functional filler to composite with polytetrafluoroethylene (PTFE) to prepare EC / PTFE composite materials. The three-dimensional interconnected carbon framework facilitates the formation of heat conduction pathways, the multi-scale porous structure improves electromagnetic wave incident and multiple reflection behavior, and the iron-doped structure enhances polarization loss and electromagnetic energy dissipation. Based on the above synergistic effects, the obtained composite material can simultaneously achieve strong electromagnetic wave absorption capability, wide effective absorption bandwidth, enhanced thermal conductivity, and good thermal cycling stability. Its minimum reflection loss can reach -55.47 dB, the maximum effective absorption bandwidth can reach 7.92 GHz, and the thermal conductivity can reach 0.45 W·m. -1 ·K -1 .
[0028] 5. Huge application potential: The material obtained by this invention has the functions of electromagnetic wave absorption, electromagnetic interference suppression and thermal management. It can be used to prepare electromagnetic wave absorbing materials, electromagnetic interference suppression materials, thermal interface materials and thermal management composite materials. In particular, it can be used in high-end electronic packaging, high-frequency communication equipment, electromagnetic protection components, radar stealth materials and lightweight integrated wave absorption / heat dissipation materials, etc., which can meet the comprehensive requirements of integrated electronic devices for electromagnetic compatibility and heat dissipation performance in a limited space. Attached Figure Description
[0029] Figure 1 The images show the morphology of the EC2 material prepared in Example 1, where (a) and (b) are transmission electron microscope (TEM) images of EC2, and (c) is a high-angle annular dark-field scanning transmission electron microscope image of EC2.
[0030] Figure 2 The image shows the HAADF image and energy-dispersive X-ray elemental mapping of the EC2 material prepared in Example 1.
[0031] Figure 3 The figures show the N2 adsorption-desorption isotherm (a) and pore size distribution curve (b) of the EC material.
[0032] Figure 4 Raman spectrum (a) and high-resolution X-ray photoelectron spectrum (b) of EC material.
[0033] Figure 5 The electromagnetic properties analysis diagram of EC material is shown in Figure 1. (a) Dielectric constant. ε r (b) Magnetic permeability μ r .
[0034] Figure 6The electromagnetic wave absorption performance diagrams for EC materials are shown below: (a) 3D RL of EC1, (b) 3D RL of EC2, (c) 3D RL of EC3, (d) 2D RL of EC1, (e) 2D RL of EC2, and (f) 2D RL of EC3.
[0035] Figure 7 The results of the thermal management performance test are as follows: (a) thermal conductivity of EC2 / PTFE sample and pure PTFE sample; (b) temperature change curves of EC2 / PTFE sample and pure PTFE sample during the heating stage; and (c) temperature change curves of EC2 / PTFE sample during the cyclic heating and cooling stages. Detailed Implementation
[0036] The present invention will be described in detail below through specific embodiments. However, the purpose and use of these illustrative embodiments are only for explaining and illustrating the present invention, and do not constitute any limitation on the actual protection scope of the present invention, nor are they intended to limit the protection scope of the present invention to these embodiments.
[0037] Example 1: Preparation of iron-doped honeycomb porous carbon (EC) materials 1. Preparation of precursor foam: Weigh 10 grams of commercially available fresh egg white and 10 grams of sodium chloride (NaCl, as a pore-forming agent) into a container, and stir vigorously with a mechanical stirrer at room temperature for 30 minutes until a uniform, fine and stable protein foam is formed.
[0038] 2. Freeze-drying: Transfer the above protein foam to a freeze dryer tray and freeze-dry under vacuum conditions until the water is completely sublimated to obtain a dry, loose, white porous protein precursor powder.
[0039] 3. Pyrolysis and Carbonization: The freeze-dried white porous protein precursor powder was transferred to an alumina crucible and placed in the isothermal zone of a tube furnace. First, high-purity argon gas was introduced into the furnace tube to purge air. Then, under continuous argon protection, the temperature was increased at a certain rate (e.g., 5 °C / min). -1 The furnace temperature was raised to 800℃ and kept at that temperature for 2 hours for pyrolysis.
[0040] 4. Template Removal and Post-treatment: After the pyrolysis process, allow it to cool naturally to room temperature. Remove the resulting black blocky product and repeatedly soak, stir, and wash it with sufficient deionized water to completely dissolve and remove the residual sodium chloride template. Dry the washed black solid product overnight in a 60°C oven, and finally grind it to obtain black iron-doped honeycomb porous carbon powder, labeled EC2.
[0041] Example 2: Preparation of Iron Single Atom Doped Honeycomb Porous Carbon (EC) Materials Iron-doped honeycomb porous carbon powder was prepared according to the method in Example 1, except that in step 1, the amount of sodium chloride used was 40g (the amount of egg white was still 10g). The resulting iron-doped honeycomb porous carbon powder was labeled EC3.
[0042] Example 3 Preparation of EC / PTFE composite material 1. The EC2 material prepared in Example 1 and a commercially available polytetrafluoroethylene (PTFE) emulsion with a solid content of 60 wt% were placed in a mixing container. The mass ratio of EC2 material to PTFE was 15:85 (i.e., the EC filling amount was 15 wt%). Then, ethanol was added to break the emulsion and the mixture was mechanically mixed to form a dough-like consistency.
[0043] 2. The dough-like mixture is placed into a mold and pressed into a sheet at room temperature with a molding pressure of 5 MPa to obtain EC2 / PTFE composite sheet.
[0044] Example 4: Preparation of EC / PTFE composite material The EC / PTFE composite material was prepared according to the method of Example 3, except that EC2 material was replaced with an equal mass of EC3 material prepared in Example 2. The final composite material was denoted as EC3 / PTFE composite material.
[0045] Comparative Example 1 The honeycomb porous carbon powder was prepared according to the method of Example 1, except that sodium chloride was not added in step 1, and the resulting honeycomb porous carbon powder was labeled as EC1.
[0046] Comparative Example 2 1. The EC1 material prepared in Comparative Example 1 and a commercially available polytetrafluoroethylene (PTFE) emulsion with a solid content of 60 wt% were placed in a mixing container. The mass ratio of EC1 material to PTFE was 15:85 (i.e., the EC filling amount was 15 wt%). Ethanol was then added to break the emulsion and the mixture was mechanically mixed to form a dough-like consistency.
[0047] 2. The dough-like mixture is placed into a mold and pressed into a sheet at room temperature with a molding pressure of 5 MPa to obtain EC1 / PTFE composite sheet.
[0048] Comparative Example 3 Pure polytetrafluoroethylene (PTFE) powder was pressed into shape using the compression molding process described in Example 3 to obtain pure PTFE sheets.
[0049] Structural characterization and performance testing of EC and EC / PTFE composite materials 1. Structural characterization and morphological observation: The microstructure of the EC material was observed using scanning electron microscopy (SEM, Thermo Fisher Scientific Verios G4 UC) and transmission electron microscopy (TEM, Spectra 300 S / TEM). The results showed that the prepared EC2 material exhibited a typical three-dimensional honeycomb interconnected porous network structure. Figure 1 a, 1b). High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images ( Figure 1 c) This indicates the presence of well-dispersed, isolated metal single-atom sites in the sample.
[0050] Furthermore, elemental composition analysis of the EC2 sample was performed using HAADF images and energy-dispersive X-ray spectroscopy elemental mapping. The resulting elemental surface mapping confirmed that carbon (C), nitrogen (N), oxygen (O), sulfur (S), and iron (Fe) elements were uniformly distributed throughout the network, verifying that the metal single-atom sites were Fe elements, and visually demonstrating its atomic-level dispersion state. Figure 2 ).
[0051] The specific surface area and pore size distribution of EC1, EC2, and EC3 materials were analyzed by nitrogen adsorption-desorption test. Figure 3 (a, 3b). As can be seen from the figure, samples EC2 and EC3 exhibit typical type IV adsorption isotherms, with EC2 having a specific surface area of 180.29 m². 2 g -1 The specific surface area of EC3 is 209.68 m². 2 g -1 The pore size distribution shows that it is mainly composed of mesopores (2-50nm), while also containing micropores and macropores, forming a hierarchical porous structure.
[0052] Tested by Raman spectroscopy (inVia Reflex) Figure 4 a) It was observed that the EC material had a distinct D peak (~1350 cm⁻¹). -1 (representing defect / disordered structure) and G peak (~1580 cm⁻¹) -1 (representing a graphitized ordered structure), and its ID / IG intensity ratio can be used to assess the degree of defect in the material. The results show that the defect levels of EC2 and EC3 are lower than those of EC1. The chemical states of N and Fe elements in EC2 material were analyzed using X-ray photoelectron spectroscopy (XPS, AXIS SUPRA). Figure 4 (b) High-resolution scanning and peak fitting of the Fe 2p and N 1s spectra revealed characteristic peaks attributable to Fe-N coordination in the Fe 2p spectrum, while the N 1s spectrum contained pyridine nitrogen and Fe-N coordination components, collectively confirming Fe-N coordination. x The formation of coordination structures.
[0053] 2. Electromagnetic wave absorption (EWA) performance test: To conduct electromagnetic parameter testing, EC1, EC2, and EC3 were mixed with PTFE at a mass ratio of 15:85 and then molded using the molding process described in Example 3 to produce a standard coaxial ring sample that meets the testing requirements. The specific dimensions are: outer diameter 7.00 mm, inner diameter 3.04 mm, and thickness 2.00 mm.
[0054] Electromagnetic parameters of standard coaxial toroidal specimens of EC2 / PTFE, EC1 / PTFE, and EC3 / PTFE were measured using a vector network analyzer (Ceyear 3672B-S) in the frequency range of 2-18 GHz. The results are as follows: Figure 5 As shown.
[0055] Based on transmission line theory, the reflection loss (RL) of the composite material at different frequencies and thicknesses was calculated using the measured complex permittivity and complex permeability. The results are as follows: Figure 6 As shown in the figure, the EC2 / PTFE composite material exhibits the best electromagnetic wave absorption performance, with the lowest reflection loss (RL) within the test frequency range. min The absorption bandwidth can reach -55.47 dB, and the corresponding effective absorption bandwidth (EAB, RL < -10 dB) can reach up to 7.92 GHz, which is significantly better than EC1 / PTFE and EC3 / PTFE composite materials.
[0056] 3. Thermal management performance test: The thermal conductivity of EC2 / PTFE composite sheet and pure PTFE sheet was measured using a thermal conductivity meter. The thermal conductivity of the pure PTFE sample was 0.195 W / m. -1 K -1 The thermal conductivity of the EC2 / PTFE composite material was increased to 0.450 W / m². -1 K -1 ( Figure 7 a) indicates that the introduction of the EC network significantly improves the thermal conductivity of the material. The dynamic heat transfer behavior of the sample was further evaluated using infrared thermal response testing. Figure 7 As shown in b, under the same heating conditions, the heating rate of the EC2 / PTFE composite material is significantly faster than that of pure PTFE, and its final stable temperature is higher than that of pure PTFE, with a temperature difference of 11.9℃. This indicates that EC2 / PTFE has a faster thermal response and stronger heat transfer capability. During the cooling process, the temperature of EC2 / PTFE also drops faster, and its temperature after cooling is lower than that of pure PTFE, with a temperature difference of 7.8℃, further demonstrating its superior heat dissipation capability. Furthermore, as... Figure 7As shown in c, EC2 / PTFE exhibits a stable and repeatable temperature response during multiple heating-cooling cycles, with no significant decay in either the peak or valley temperatures, indicating that the composite material has good cyclic thermal stability and reliable thermal management performance.
[0057] 4. Experimental Results and Conclusions The above experimental results demonstrate that this invention, using egg white as a biomass precursor, utilizing bubbles in protein foam as soft templates and pore-forming units, and sodium chloride as a hard template and pore-forming agent, prepares egg white-derived iron-doped porous carbon material (EC) with a three-dimensional honeycomb multi-scale porous structure through freeze-drying, pyrolysis, and washing. In this material, C, N, O, Fe, and S elements are uniformly distributed, and iron elements do not show significant agglomeration, which is conducive to the formation of atomically dispersed iron single-atom sites or Fe–N sites. x Coordination structure. EC / PTFE composites were prepared by combining the obtained EC material with polytetrafluoroethylene (PTFE) at a filler content of 15 wt%. Experimental results show that the resulting composite material maintains the processability and flexibility of the polymer matrix while possessing both electromagnetic wave absorption and thermal management properties. Specifically, the EC2 / PTFE composite material exhibits a minimum reflection loss of -55.47 dB, a maximum effective absorption bandwidth of 7.92 GHz, and a thermal conductivity of 0.450 W / m². -1 K -1 The aforementioned performance improvements are primarily attributed to the structural advantages and synergistic effects of the components in egg white-derived iron single-atom doped porous carbon materials. On one hand, the three-dimensional honeycomb multi-scale porous structure helps improve impedance matching, extend the electromagnetic wave propagation path, and promote multiple reflections, interface polarization, and conductivity loss. On the other hand, the atomically dispersed iron single-atom sites or Fe–N... x The coordination structure can induce local charge redistribution, enhancing polarization loss and electromagnetic energy attenuation. Simultaneously, the continuous carbon framework provides an effective pathway for heat transfer, and the local carbon structure regulation induced by iron single atoms is beneficial for improving thermal conductivity within the carbon phase. Therefore, the EC / PTFE composite material provided by this invention can achieve synergistic integration of electromagnetic wave absorption, electromagnetic interference suppression, and thermal management functions within the same material system, and can be used in fields such as electronic packaging, thermal interface materials, communication equipment, electromagnetic protection, and integrated electromagnetic absorption and heat dissipation materials.
Claims
1. A method for constructing egg white-derived iron single-atom-doped porous carbon materials using a soft and hard dual-template approach, characterized in that... Includes the following steps: (1) Mix egg whites with sodium chloride and stir vigorously to form stable protein foam; (2) The protein foam obtained in step (1) is freeze-dried under vacuum to obtain a porous protein precursor; (3) The porous protein precursor obtained in step (2) is subjected to pyrolysis under an inert atmosphere; (4) After pyrolysis, the product is cooled, the sodium chloride template is removed by washing with water, and then dried to obtain iron single-atom doped porous carbon material.
2. The method according to claim 1, characterized in that: In step (1), the mass ratio of egg white to sodium chloride is 1:1-4.
3. The method according to claim 1, characterized in that: In step (1), the stirring speed is greater than or equal to 800 r / min.
4. The method according to claim 1, characterized in that: In step (3), the pyrolysis temperature is 750-850℃ and the pyrolysis time is 2-3h.
5. Iron-doped porous carbon material prepared according to any one of claims 1-4.
6. A single-atom-doped porous carbon / polytetrafluoroethylene composite material, characterized in that: It is composed of the iron single-atom doped porous carbon material as described in claim 5 and polytetrafluoroethylene.
7. The iron-doped porous carbon / polytetrafluoroethylene composite material according to claim 6, characterized in that: Iron single-atom doped porous carbon materials account for 15 wt% of the total mass of iron single-atom doped porous carbon materials and polytetrafluoroethylene.
8. The iron-doped porous carbon / polytetrafluoroethylene composite material according to claim 6, characterized in that: The composite material is made by mixing iron-doped porous carbon material with polytetrafluoroethylene emulsion, followed by demulsification with ethanol and stirring to form a dough-like mixture, which is then pressed into shape in a mold.
9. The application of the iron single-atom doped porous carbon material of claim 5, and the iron single-atom doped porous carbon / polytetrafluoroethylene composite material of claim 6, 7 or 8 in electromagnetic wave absorbing materials, electromagnetic interference suppressing materials, thermal interface materials, and thermal management composite materials.